Assessment of Energy Efficient HVAC Systems for Office Buildings - Özpolat, Yunus Emre; Kara, Yusuf Ali (Bursa Teknik Üniversitesi, 2022)
As a result of economic and political requirements, renewable energy investments are supported with various incentives all over the world, while fossil fuel systems are restricted by regulations. This article aims to make conventional heating, cooling and power systems more efficient or to develop an alternative system based on renewable energy by modeling an office building. Considering three scenarios - classical heating-cooling system, combined cooling-heating-power system and zero energy building, the test building’s energy estimation analysis and life-cycle cost analysis have been conducted and 3 different sub-scenarios for renewable energy scenarios have been generated. As a result of the Hourly Analysis Program (HAP), the building’s cooling design load was found to be 742.7 kW, and the heating design load was 439.8 kW. The required borehole length for ground source heat pump is determined as 20,371 m for cooling and 9,137 m for heating, while the heat is discharged into the borehole with a rate of -44.3 W / m and extracted with a rate of 34 W / m. Annual energy generation of the photovoltaic plant was determined as 607.639 kWh and installed power of for this plant was calculated as 463 kWp. Lifecycle cost analyses were performed by using P1-P2 method and according to the calculations, the payback period for the extra investment cost is 37 months for the combined cooling-heating-power plant, whereas it is 94 months for the improved zero energy building design. Similarly, the payback period for the full investment cost is determined as 58 months for the combined cooling-heating-power plant, and 127 months for the improved zero energy building design. As a result, a hybrid zero energy building (air source condenser + ground source heat pump, photovoltaic panels) is proposed as the best design option for the office building identity.
Keywords: Engineering; Mühendislik